PEMIKIRAN EKONOMI IMAM AL-GHAZALI: ANALISIS KONSEP KEPEMILIKAN, UANG, DAN ETIKA PASAR DALAM IHYA ULUMUDDIN - Dina Sari; Salma Agita Sitepu; Ratna Sari Hasibuan; Gemma Surya Gemilang; Fitri Hayati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study explores the economic thought of Imam Al-Ghazali as presented in Ihya Ulumuddin, focusing on three main concepts: ownership, money, and market ethics. The research adopts a library research method with a qualitative approach and content analysis to examine Al-Ghazali’s perspectives in depth. The findings reveal that Al-Ghazali rejects the notion of absolute ownership of wealth, viewing it instead as a trust (amanah) from Allah that must be managed responsibly and justly. Regarding money, he defines it as a legitimate medium of exchange and strongly criticizes the practices of usury (riba) and hoarding (iktinaz), which he considers harmful to economic balance and social justice. In the realm of market ethics, Al-Ghazali emphasizes honesty, fairness, prohibition of monopoly (ihtikar), and sincere intentions in economic activities. His thoughts remain highly relevant to contemporary economic discourse, particularly in the development of a just, sustainable, and morally grounded Islamic economic system